2021
DOI: 10.3390/su13074074
|View full text |Cite
|
Sign up to set email alerts
|

Matching and Mismatching of Green Jobs: A Big Data Analysis of Job Recruiting and Searching

Abstract: Creating green jobs tackles two crises: the economic downturn and environmental degradation. Responding to the economic downturn, some governments have declared a “green new deal” to remedy unemployment and the economic crisis. Job creation has been suggested as a driving force for sustainable economic development and climate change action. However, the question of how many and what types of green jobs are required has not been systematically examined. Are green job openings and searches matching each other in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…Sustainability jobs, on the other hand, appear in articles related to strategy formulation. Authors of publications seeking scientific novelty create new names for already defined terms, which is why constructs such as “ecojobs” appear [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sustainability jobs, on the other hand, appear in articles related to strategy formulation. Authors of publications seeking scientific novelty create new names for already defined terms, which is why constructs such as “ecojobs” appear [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, solutions were sought to find a way out of the crisis. It was noted that the current paradigm of economic development, which is mainly based on non-renewable resources, is unreliable and does not provide opportunities for future generations [ 77 , 79 ]. The researchers, therefore, drew attention to the need to implement sustainable development and related green jobs into economic practice [ 80 , 81 ].…”
Section: Discussionmentioning
confidence: 99%
“…This list of the areas or factors influencing the GJs creation process then is not used in a mathematical method to predict or calculate the number of the GJs but to prove transformation toward the CE (McMahon et al 2021;Rojas Arboleda et al 2021). The majority of the quantitative publications document the number of GJs (Ferrão et al 2015) or are focused on the gap between demand and supply of GJs (Song et al 2021). However, in the literature, there is a similarity to be presented in this paper, graphical approach describing the relations between GJs and CE (Horbach et al 2015); these works are qualitative in their methods (Battaglia et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Following the scrutiny of the selected literature, one can easily presume that many studies have chosen to begun to approach green jobs in line with the "Green Jobs Initiative" description issued by the partnership between the United Nations Environment Program (UNEP), the International Trade Union Confederation (ITUC), the International Organization of Employers (IOE) and the International Labor Organization (ILO). Thus, the studies conducted by: [18,19,21,22,[25][26][27][28][30][31][32][33][34] assess green jobs in terms of their ability to decrease the impact on the environment to a level that falls within the range of sustainability. Such jobs involve reducing the consumption of energy, raw materials, and water by adopting and implementing highly efficient strategies aimed at "decarbonizing the economy and reducing greenhouse gas emissions, to minimize or completely avoid all forms of waste and pollution, to protect and restore ecosystems and biodiversity" [32], in line with the "Green Jobs Initiative" [2].…”
Section: "Green Jobs" Meanings In the Literaturementioning
confidence: 99%
“…Song et al, analyzing the supply and demand of green jobs based on data provided by online recruitment services (Ecojob site) on the South Korean labor market from 2009 to 2020, have revealed that green jobs are concentrated in the Seoul and Gyeounggi-do metropolitan areas, where the number of jobs related to water and air quality is high [26]. Their conclusions suggest that green job creation policy should reflect data on regional and sectoral timing, demand, and supply.…”
Section: Related Research Areasmentioning
confidence: 99%